Rethinking the Link between Global Economic Conditions and Oil Prices: A Quantile Perspective - Raggad, Bechir; Talmoudi, Ramzi; Zarai, Mohamed (Journal of Cultural Analysis and Social Change, 2025)
This study examines the dynamic interactions between WTI and BRENT crude oil prices and the Global Economic Conditions (GEC) index from May 1987 to October 2025. Using conventional unit root and linear Granger causality tests, we find that oil prices are non-stationary in levels, while GEC is stationary, and that linear causality is weak and asymmetric. To capture heterogeneous effects across market conditions, we apply Granger-causality-in-quantiles (Troster, 2018), revealing strong nonlinear and quantile-dependent relationships. Results show that GEC predominantly drives WTI across extreme market conditions, whereas Brent exhibits bidirectional causality with GEC, particularly in moderate-to-high volatility regimes. Overall, the evidence points out the presence of tail-dependent effects. It suggests that policy makers and investors should interpret oil-economic relationships considering the underlying market regime.